A Baptismal Ecclesiology of Inclusion for Every Body. Issue 3 (October 2022) - Conner, Benjamin T.
The youth involved in the Missing Voices Project research have intuited and drawn upon some of the central theological themes from disability theology. These youth bear witness to a nascent and youthful theology of disability along with elements of an inclusive, activist ecclesiology.